Fractal dimension and anisotropy of soil CO2 emission in an agricultural field during fallow - La Scala, N. [UNESP] (2009)
The study of soil CO2 emission is a relevant task due to the fact that it is related to many environmental issues, especially the enhanced greenhouse effect. In this work we investigated the spatial variability structure of a bare soil CO2 emission in an area of 80 x 80 m, during twelve different days. Spatial and temporal variability analyses in the 65-point grid indicate that significant spatial heterogeneity is present in most of the days. Fractal dimension values varying from 2 to 2.88 was determined in a direction of 84.3 +/- 22.5 degrees, which is close to perpendicular of crop lines. This effect seems to be related to the structure of temporal variability of Soil CO2 emission, which presents a complex net of correlation with 83% of grid points connected within the same cluster, also with most of the points aligned perpendicular to crop lines.